*Not* So Fast: A Response to Augustine’s Critique of the BICS Contest - Braude, Stephen; Barušs, Imants; Delorme, Arnaud; Radin, Dean; Wahbeh, Helané (Journal of Scientific Exploration, 2022)
Keith Augustine’s critical evaluation of the essay contest sponsored by the Bigelow Institute of Consciousness Studies (BICS) is an interesting but problematic review. It mixes reasonable and detailed criticisms of the contest and many of the winning essays with a disappointing reliance on some of the most trite and superficial criticisms of parapsychological research. Ironically, Augustine criticizes the winning essays for using straw-man arguments and cherry-picked evidence even though many of his own arguments commit these same errors.